2009
DOI: 10.1093/jaoac/92.5.1327
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Vitamin D in Foods and Nutritional Supplements by Liquid Chromatography/Tandem Mass Spectrometry

Abstract: Vitamin D is a fat-soluble vitamin with great nutritional interest. An HPLC/MS/MS method was developed to measure vitamin D with atmospheric pressure chemical ionization. Under the experimental parameters used, the LOQ was 0.018 IU/g or 0.45 ng/g, which greatly enhances the capability of measurement of vitamin D at low levels in foods and supplements. This method was validated with spike recovery of 100 15 and the RSD of less than 10 for most sample matrixes, including infant formula, cheese, cereal and cereal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…It is important to note that the elution sequence of the peaks might be altered when using different columns. When using a C30 column, pre-D eluted after vitamin D. [9] However, under the LC conditions described here, with a Hypersil column, pre-D eluted before vitamin D, with retention times of 3.2 and 3.4 min, respectively. Good separation between pre-D and vitamin D was also achieved for vitamin D 2 and all of the isotope-labeled vitamin D compounds studied in this work.…”
Section: Separation Of Pre-d From Vitamin Dmentioning
confidence: 79%
See 2 more Smart Citations
“…It is important to note that the elution sequence of the peaks might be altered when using different columns. When using a C30 column, pre-D eluted after vitamin D. [9] However, under the LC conditions described here, with a Hypersil column, pre-D eluted before vitamin D, with retention times of 3.2 and 3.4 min, respectively. Good separation between pre-D and vitamin D was also achieved for vitamin D 2 and all of the isotope-labeled vitamin D compounds studied in this work.…”
Section: Separation Of Pre-d From Vitamin Dmentioning
confidence: 79%
“…High-performance liquid chromatography (HPLC) has been widely used for the measurement of vitamin D. [2,3] However, with high sensitivity and high selectivity, liquid chromatography/mass spectrometry (LC/MS) has become more popular for vitamin D measurement recently. [4][5][6][7][8][9][10][11][12][13][14][15] Heudi et al [8] reported an LC/MS method for measurement of vitamin D 3 and other fat-soluble vitamins in infant formula with vitamin D 2 as internal standard. Dimartino [5,6] used LC/MS to measure vitamin D 3 in cheese and other foods, also with D 2 as the internal standard for measurement of D 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The analyses were conducted according to methodology reported by Huang et al (2009). Briefly, a 2-10 g subsample of the homogenized food, with internal standard added ([ 2 H 3 )cholecalciferol for vitamin D 3 , [ 2 H 3 ]25-hydroxycholecalciferol for 25(OH)D 3 , and [ 2 H 3 ]ergocalciferol for vitamin D 2 ) (> 95%; ISO Sciences, Ambler, PA, USA), was subjected to overnight alkaline saponification in alcoholic KOH, under nitrogen and with 2% pyrogallic acid added.…”
Section: Vitamin D Analysismentioning
confidence: 99%
“…A key part of this work was validating methods for vitamin D and 25(OH)D. Until recently, methods for vitamin D were generally not standardized and often gave disparate results between laboratories using similar methods Phillips et al, 2008). More recently, methodology for measurement of vitamin D and 25(OH)D by LC-MS has been validated (Byrdwell, 2009;Huang et al, 2009). The USDA Nutrient Data Laboratory (Beltsville, MD) has demonstrated that it is possible to obtain consistent results for vitamin D 3 and 25(OH)D 3 among laboratories .…”
Section: Introductionmentioning
confidence: 99%